The missing voices of Indigenous Australians in the social, cultural and historical experiences of tuberculosis: a systematic and integrative review - Sue Devlin; David MacLaren; Peter D Massey; Richard Widders; Jenni A Judd (BMJ Global Health)
Introduction Disparities in tuberculosis (TB) rates exist between Indigenous and non-Indigenous populations in many countries, including Australia. The social determinants of health are central to health inequities including disparities in TB rates. There are limitations in the dominant biomedical and epidemiological approaches to representing, understanding and addressing the unequal burden of TB for Indigenous peoples represented in the literature. This paper applies a social determinants of health approach and examines the structural, programmatic and historical causes of inequities for TB in Indigenous Australia.Methods Aboriginal Australians’ families in northern New South Wales who are affected by TB initiated this investigation. A systematic search of published literature was conducted using PubMed, PsycINFO, Scopus and Informit ATSIhealth databases, the Australian Indigenous Health, InfoNet and Google. Ninety-five records published between 1885 and 2019 were categorised and graphed over time, inductively coded and thematically analysed.Results Indigenous Australians’ voices are scarce in the TB literature and absent in the development of TB policies and programmes. Epidemiological reports are descriptive and technical and avoid analysis of social processes involved in the perpetuation of TB. For Indigenous Australians, TB is more than a biomedical diagnosis and treatment; it is a consequence of European invasion and a contributor to dispossession and the ongoing fight for justice. The introduction and spread of TB has resulted in the stealing of lives, family, community and cultures for Indigenous Australians. Racist policies and practices predominate in the experiences of individuals and families as consequences of, and resulting in, ongoing structural and systematic exclusion.Conclusion Development of TB policies and programmes requires reconfiguration. Space must be given for Indigenous Australians to lead, be partners and to have ownership of decisions about how to eliminate TB. Shared knowledge between Indigenous Australians, policy makers and service managers of the social practices and structures that generate TB disparity for Indigenous Australians is essential.A social determinant of health approach will shift the focus to the social structures that cause TB. Collaboration with Indigenous partners in research is critical, and use of methods that amplify Indigenous peoples' voices and reconfigure power relations in favour of Indigenous Australians in the process is required.